Signals of selection beyond bottlenecks between exotic populations of the bull‐headed dung beetle, Onthophagus taurus. Issue 2 (1st February 2021) - Pespeni, Melissa H.; Moczek, Armin P.
Abstract: Colonization of new environments can lead to population bottlenecks and rapid phenotypic evolution that could be due to neutral and selective processes. Exotic populations of the bull‐headed dung beetle ( Onthophagus taurus ) have differentiated in opposite directions from native beetles in male horn‐to‐body size allometry and female fecundity. Here we test for genetic and transcriptional differences among two exotic and one native O. taurus populations after three generations in common garden conditions. We sequenced RNA from 24 individuals for each of the three populations including both sexes, and spanning four developmental stages for the two exotic, differentiated populations. Identifying 270, 400 high‐quality single nucleotide polymorphisms, we revealed a strong signal of genetic differentiation between the three populations, and evidence of recent bottlenecks within and an excess of outlier loci between exotic populations. Differences in gene expression between populations were greatest in prepupae and early adult life stages, stages during which differences in male horn development and female fecundity manifest. Finally, genes differentially expressed between exotic populations also had greater genetic differentiation and performed functions related to chitin biosynthesis and nutrient sensing, possibly underlying allometry and fecundity trait divergences. Our results suggest that beyond bottlenecks, recent introductions have led to genetic and transcriptional differences in genes correlated with observed phenotypic differences. Abstract : Highlights: Common garden transcriptomics reveals neutral and selective processes led to rapid allelic and transcriptional divergence in specific functional classes of genes and developmental stages among exotic populations of the bull‐headed dung beetle.